USLŪB ALHᾹKIM DALAM AL QURAN - Kainuzah, Fatkhan Alief; Khoirurrosi, Khoirurrosi; Aghnia, Charity Dinda; Rosi, Fathor; Wafa, Ali (STIQ Amuntai, 2023)
Research on uslub Al Hākim in the Quran aims to understand and analyze the effective and appropriate methods of conveying the Quran's messages. The Quran is a comprehensive guide to life and contains many language styles. Studying the wise style helps extract wisdom and lessons from the Quranic verses and understand its communication strategies. Effectively conveying the Quran in the letters Al-Baqorah, Ali Imran, Al-Māidah, Al-An'ām, Al-A'rāf, Al-Anfāl, Yūsuf, Al-Ra'ad, Al-Isrā', messages requires understanding language styles and choosing the appropriate words. The research aims to identify and classify verses with wise styles based on their form, topic, and meaning. The research methodology used is qualitative descriptive and content analysis. The researcher relies on the verses of the Quran as the primary data source and utilizes other reference sources. The wise style involves addressing the audience with an unexpected meaning and responding to a question with something other than what was expected. It relies on three pillars: the addressed, the addressing, responding with the unexpected, and considering the addressee's priority. It aims to raise awareness about important matters or shift the conversation to another topic.